White Space Networking with Wi-Fi like Connectivity - Bahl, Victor; Chandra, Ranveer; Moscibroda, Thomas; Murty, Rohan; Welsh, Matt (SIGCOMM 2009: ACM SIGCOMM Conference on Applications, Technologies, Architectures, and Protocols for Computer Communications, Barcelona, Spain, 2009)
Networking over UHF white spaces is fundamentally different from conventional Wi-Fi along three axes: spatial variation, temporal variation, and fragmentation of the UHF spectrum. Each of these differences gives rise to new challenges for implementing a wireless network in this band. We present the design and implementation of WhiteFi, the ﬁrst Wi-Fi like system constructed on top of UHF white spaces. WhiteFi incorporates a new adaptive spectrum assignment algorithm to handle spectrum variation and fragmentation, and proposes a low overhead protocol to handle temporal variation. WhiteFi builds on a simple technique, called SIFT, that reduces the time to detect transmissions in variable channel width systems by analyzing raw signals in the time domain. We provide an extensive system evaluation in terms of a prototype implementation and detailed experimental and simulation results.